Autism, Emotion Recognition and the Mirror Neuron System: The Case of Music - Molnar-Szakacs, Istvan (McGill University, 2009)

(untitled)
Understanding emotions is fundamental to our ability to navigate and thrive in a complex world of human social interaction. Individuals with Autism Spectrum Disorders (ASD) are known to experience difficulties with the communication and understanding of emotion, such as the nonverbal expression of emotion and the interpretation of emotions of others from facial expressions and body language. These deficits often lead to loneliness and isolation from peers, and social withdrawal from the environment in general. In the case of music however, there is evidence to suggest that individuals with ASD do not have difficulties recognizing simple emotions. In addition, individuals with ASD have been found to show normal and even superior abilities with specific aspects of music processing, and often show strong preferences towards music. It is possible these varying abilities with different types of expressive communication may be related to a neural system referred to as the mirror neuron system (MNS), which has been proposed as deficient in individuals with autism. Music’s power to stimulate emotions and intensify our social experiences might activate the MNS in individuals with ASD, and thus provide a neural foundation for music as an effective therapeutic tool. In this review, we present literature on the ontogeny of emotion processing in typical development and in individuals with ASD, with a focus on the case of music.